AUDIT CERTIFICATE AND FINANCIAL MANAGEMENT ACCOUNTABILITY INDEX LEVEL OF LOCAL AUTHORITIES IN KEDAH, 2002-2019 (Journal of Governance and Development (JGD), 2024)
Financial Management Accountability Index is a government indicator to empowers the level of financial compliance of public agencies. Previous studies often outlined issues related to leakage and misuse of funds among public officials. Therefore, this article generally examines the financial management performance of Local Authorities or Pihak Berkuasa Tempatan (PBT) in Kedah for the year 2002 to 2019. Several years of data were obtained from the National Audit Report and descriptive analysis in the form of patterns and trends was made to identify the type of audit certificate and accountability index score (IA) of financial management issued by the National Audit Department (JAN) on financial reporting of 11 PBTs in Kedah. The results show that there are no significant differences from the findings by other researchers in the last two decades. It has been found that the majority of 63 per cent (n = 7) PBTs still get a Reprimanded Certificate (UO), often involving record registers such as Vote Book, Capital Assets Register, and Log Book that is not satisfactorily maintained in addition to expenses over approved allocation. However, the overall IA issued by JAN from 2007 to 2019 showed an “Excellent” score of 33.9 per cent (n = 20), a “Good” of 59.3 per cent (n = 35) and a “Satisfactory” of 6.8 per cent (n = 4 ) to 11 PBTs in Kedah. During those 18 years, most of the PBTs in Kedah worked to increase the level of accountability and compliance of their respective financial management shown by better records every year.